Wide belt sowing improves the grain yield of bread wheat by maintaining grain weight at the backdrop of increases in spike number - Zhang, Xiu; Hua, Yifan; Liu, Yunjing; He, Mingrong; Ju, Zhengchun; Dai, Xinglong (Frontiers in Plant Science, 2022)
Increasing the seeding belt width from 2–3 cm (conventional drilling, CD) to 8–10 cm (wide belt sowing, WB) can markedly improve the grain yield of bread wheat. However, there are insufficient data to explain how WB affects dry matter (DM) remobilization, pre- and post-anthesis production, and ultimately grain weight and grain yield. In the present study, four bread wheat cultivars (Jimai44, Taishan27, Gaoyou5766, and Zhouyuan9369) with similar phenology characteristic were selected as experimental materials and two sowing patterns (CD and WB) were applied during the 2018–2019 and 2019–2020 growing seasons, to investigate the effects of sowing pattern on grain yield and its components of bread wheat. The results showed that WB increased the post-anthesis rate of canopy apparent photosynthesis (CAP) in comparison with CD, by 19.73–133.68%, across the two seasons and four bread wheat cultivars. Furthermore, WB significantly increased the activities of superoxide dismutase, peroxidase, and catalase, and decreased the malondialdehyde content of the flag and penultimate leaf, thereby extending the duration of the high-value CAP period by 1.95–2.51 days. The improved rate and duration of CAP in WB led to an increase in post-anthesis DM production of 13.33–23.58%, thus ensuring DM distribution to the grain of each bread wheat cultivar. Consequently, in WB, the grain weight was maintained, the grain yield was increased markedly by 9.65–15.80%, at the backdrop of increases in spike number and in turn grain number per unit area. In summary, WB could be applied widely to obtain a high yield of bread wheat.